Implementation of Active, Innovative, Creative, Effective, and Enjoyable Learning Models (PAIKEM) in Islamic Religious Education (PAI) Subjects in Grade VII Darul Ishlah Junior High School in the 2024/2025 Academic Year (Lembaga Pengembangan Kinerja Dosen, 2025)
Teachers are required to adopt a wise and thoughtful approach in teaching, since their perception of students will influence their attitudes and actions. Not all teachers assess students in the same way, and this affects the methods they apply in the classroom. To achieve optimal learning outcomes, teachers must take on new roles as facilitators, mediators, learning partners, and evaluators. This means creating a democratic and dialogical learning atmosphere between teachers and students, as well as among students themselves. One effective way is by applying the PAIKEM learning model (Active, Innovative, Creative, Effective, and Enjoyable). This study aims to: (1) Describe the implementation of the PAIKEM model in Islamic Religious Education for Grade VII at Darul Ishlah Junior High School. (2) Describe the obstacles encountered in applying this model. The research uses a qualitative approach with interviews, observation, and documentation as data collection techniques. Data analysis was conducted through reduction, presentation, and conclusion drawing. The results indicate that the PAIKEM model has been implemented well, through discussions, opportunities for students to express opinions, group assignments, interactive communication, motivation, use of media such as videos, and enjoyable memorization. However, challenges include limited learning media, teachers’ creativity that is not yet optimal, inadequate facilities and infrastructure, and low student motivation.